Telematic Simulation as Experiential Learning of English - Amparo García-Carbonell; Frances Watts; Mª Ángeles Andreu-Andrés (Universitat Politècnica de València, 2012)
This paper outlines the principles of simulation and gaming methodology and describes the teaching strategy of telematic simulation used with Spanish engineering students in a course of English as a foreign language at advanced level. Telematic simulation creates an environment that allows multidisciplinary groups of students from all over the world to interact; their language of communication is English, with which they discuss, negotiate and reach agreements on topics of current interest which are posed in the scenario. The effectiveness of the methodology in a specific context was demonstrated in a quasi-experimental study in which the improvements in reading comprehension, listening comprehension, grammar and writing were measured. The results of the study provide the evidence to affirm that this approach to teaching and learning can guarantee significant learning of English at advanced level. The methodology encourages the experiential learning of the language and, at the same time, entails the added value of the acquisition of professional competences.